2016
DOI: 10.1186/s13231-016-0021-2
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology and management of reperfusion injury and hyperperfusion syndrome after carotid endarterectomy and carotid artery stenting

Abstract: Cerebral hyperperfusion is a relatively rare syndrome with significant and potentially preventable clinical consequences. The pathophysiology of cerebral hyperperfusion syndrome (CHS) may involve dysregulation of the cerebral vascular system and hypertension, in the setting of increase in cerebral blood flow. The early recognition of CHS is important to prevent complications such as intracerebral hemorrhage. This review will focus on CHS following carotid endarterectomy and carotid artery stenting. We will dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 37 publications
1
95
0
10
Order By: Relevance
“…Moreover, BP control may be challenging, and even when there is normal BP, CHS can occur 9. Abou-Chebl et al 10 strictly maintained BP at <120/80 mm Hg in patients at high risk of CHS and found a significant decrease in the incidence of CHS and ICH.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, BP control may be challenging, and even when there is normal BP, CHS can occur 9. Abou-Chebl et al 10 strictly maintained BP at <120/80 mm Hg in patients at high risk of CHS and found a significant decrease in the incidence of CHS and ICH.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies show that there might be a role of transforming growth factor beta (TGFβ) signaling pathway. [13][14][15]…”
Section: Chronic Hypertension and Related Vascular Changesmentioning
confidence: 99%
“…Clinical presentation includes acute neurological deficits such as new onset headache, seizures, hemiparesis or intracerebral haemorrhage. Early detection of the CHS is paramount to administer an appropriate management and decrease the likelihood of cerebral injury 2. CT perfusion has been proposed as a predictive tool for CHS in patients receiving intervention for carotid stenosis,3 and it is suitable to provide evidence of hyperperfusion and guide medical treatment.…”
Section: Descriptionmentioning
confidence: 99%